An overview of forensic operations performed following the terrorist attacks on November 13, 2015, in Paris - Antoine Tracqui; Céline Deguette; Tania Delabarde; Yann Delannoy; Isabelle Plu; Isabelle Sec; Lilia Hamza; Marc Taccoen; Bertrand Ludes (Oxford University Press, 2020)
On the evening of November 13, 2015, the city of Paris and its surroundings was hit by a series of attacks committed by terrorist groups, using firearms and explosives. The final toll was 140 people deceased (130 victims and 10 terrorists or their relatives) and more than 413 injured, making these attacks the worst mass killings ever recorded in Paris in peacetime. This article presents the forensic operations carried out at the Medicolegal Institute of Paris (MLIP) following these attacks. A total of 68 autopsies of bodies or body fragments and 83 external examinations were performed within 7 days, and the overall forensic operations (including formal identification of the latest victims) were completed 10 days after the attacks. Over this period, 156 body presentations (some bodies were presented several times) were provided to families or relatives. Regarding the 130 civilian casualties, 129 died from firearm wounds and one died from blast injuries after an explosion. Of the 10 terrorists or their relatives who were killed, eight died from suicide bombing, one was shot by police and one died from crush injuries due to partial collapse of a building following the police raid against a terrorist's hideout after the attacks. All mass shootings were perpetrated with AK-47 or Zastava M70 assault rifles using 7.62 mm × 39 mm cartridges. In the case of ballistic injuries, death was most often obviously caused by craniocerebral injuries, extensive organ lacerations and/or massive haemorrhage. Among the terrorists killed by bombing, the lesion patterns were body transection, multiple amputations, extreme organ lacerations and the presence of foreign bodies owing to the shrapnel load (steel nuts, glass fragments) or the explosive charge fastening system of the devices. This discussion highlights the particular difficulties of interpretation encountered within the framework of ballistic injuries, a conclusion that should lead to a modest and realistic approach in these exceptional situations where forensic operations involve a very large number of victims in a constrained time.